Upaya Peningkatan Pengetahuan dan Kewaspadaan Terhadap Gangguan Neurologi Melalui Pemeriksaan dan Edukasi Kesehatan - Padmiswari, Anak Agung Istri Mas; Wulansari, Nadya Treesna; Harditya, Kadek Buja (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Neurological disorders are among the growing public health problems associated with aging and lifestyle changes. Lack of knowledge and awareness of early neurological symptoms often hinders efforts in early detection and prevention. This community service activity aimed to enhance public knowledge and awareness of neurological disorders through health examinations and educational interventions. The program was conducted in Renon Village, involving 50 participants from the general public and elderly groups. The methods included pre-test, basic neurological health screening, interactive health education, and post-test evaluation. The results showed a 32% increase in participants’ average knowledge scores after the intervention, with 22.4% of participants identified as having potential neurological risk factors such as hypertension, hyperglycemia, and decreased reflexes. The improvement in knowledge and community participation demonstrated the effectiveness of the participatory approach applied. These findings support the importance of integrating medical screening and community-based education as preventive strategies to maintain neurological health.